ANALISIS PENGARUH KEBIJAKAN DEVIDEN, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN UTANG PERUSAHAAN - Loh Wenny Setiawati; Jane Kristani (Magister Akuntansi, Universitas Atma Jaya Makassar, 2018)
In order to gain profit, companies need to manage their capital. One element to note is how big the company is able to meet the needs of funds that will be used to generate profits for the company. The funds can be obtained from external parties, and set in the corporate debt policy. Debt policy is a liability taken by the management in order to obtain the source of financing for the company so that it can be used to finance the company's operational activities. This research uses multiple linier regression analysis method that will test the influence of dividend policy, firm size, sales growth and managerial ownership to corporate debt policy. The samples used in this study are 103 manufacturing companies listed on the Indonesia Stock Exchange during the period 2012 - 2014. The results of this research indicate that firm size, sales growth affect the corporate debt policy, while dividend policy and managerial ownership have no effect on corporate debt policy.